Self-organized learning strategy for graduate students (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify self-organized learning strategies for graduate students at the university of Tikrit, and the research sample consisted of (50) students from the department of Educational and psychological sciences in the college of education for Human sciences, The results of the research found that postgraduate students possess self-organized learning